2019
DOI: 10.2106/jbjs.oa.19.00015
|View full text |Cite
|
Sign up to set email alerts
|

Floor and Ceiling Effects, Time to Completion, and Question Burden of PROMIS CAT Domains Among Shoulder and Knee Patients Undergoing Nonoperative and Operative Treatment

Abstract: The purpose of this form is to provide readers of your manuscript with information about your other interests that could influence how they receive and understand your work. The form is designed to be completed electronically and stored electronically. It contains programming that allows appropriate data display. Each author should submit a separate form and is responsible for the accuracy and completeness of the submitted information. The form is in six parts. Identifying information. The work under considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 48 publications
0
49
0
Order By: Relevance
“…5,6 With the addition of these measures, PROMIS has reduced redundant questions while addressing multiple modalities, therefore reducing the number of responses required to provide an outcome score assessment in comparison with legacy PROs, while providing accurate health state estimations across specialties. 7,8 PROMIS also has been shown to be an effective and efficient tool for reporting patient outcomes in various orthopaedic surgery procedures [9][10][11] and has strongly correlated with common legacy PROs. 12,13 It is well established within the literature that hip arthroscopy is an effective treatment for femoroacetabular impingement syndrome (FAIS) and leads to improvement in PROs over time.…”
mentioning
confidence: 99%
“…5,6 With the addition of these measures, PROMIS has reduced redundant questions while addressing multiple modalities, therefore reducing the number of responses required to provide an outcome score assessment in comparison with legacy PROs, while providing accurate health state estimations across specialties. 7,8 PROMIS also has been shown to be an effective and efficient tool for reporting patient outcomes in various orthopaedic surgery procedures [9][10][11] and has strongly correlated with common legacy PROs. 12,13 It is well established within the literature that hip arthroscopy is an effective treatment for femoroacetabular impingement syndrome (FAIS) and leads to improvement in PROs over time.…”
mentioning
confidence: 99%
“…Moderate ceiling (floor) effects are defined by > 10%, minor by > 5%, and negligible by < 5% of the sample (35).…”
Section: Discussionmentioning
confidence: 99%
“…When functionally impaired knee or shoulder surgery patients were surveyed, 1 study found negligible ceiling and floor effects (<2% for PROMIS-PF and PROMIS-PI). 6 Still, some studies have identified varying levels of ceiling and floor effects for PRO-MIS-CAT in impaired patient populations undergoing orthopaedic procedures. Ceiling effects as great as 28% were identified in patients undergoing upper extremity fracture care, 5 and floor effects as great as 19% were identified in patients undergoing cervical spine surgery.…”
Section: Discussionmentioning
confidence: 99%